ROLE OF STATE IN FORMATION OF SOCIO-CULTURAL ENVIRONMENT AS YOUTH SOCIALIZATION FACTOR (Archive of Conferences, 2021)
The article considers the problem of social and cultural environment as the most comprehensive and universal factor affecting the process of younger generation socialization, and determines the place of the state and public policy in the micro- and macro-environment. The study arrives at a conclusion that the processes of socialization and individualization are inextricably linked to the natural rights of man, since they allow young people, while satisfying their needs, not to infringe the rights of other individuals. Depending on a socio-cultural environment, the man forms his own set of values and needs, the satisfaction of which makes up the aim of his life. The factors directly affecting youth socialization have been established, and namely: the macro-environment – a society with its continual transformations and revision of certain norms, values, as each stage of a society’s life and development calls for a new type of personality; micro-environment – an immediate environment of the individual, his standards, requirements, expectations, and attitudes; a personality proper – its qualities, through which the process of individualization and simultaneously that of socialization take place, since these processes form two sides of one holistic phenomenon.